Hubungan Di Antara Konsep Kendiri Dengan Kemahiran Komunikasi Terhadap Pencapaian Akademik Pelajar Di Sekolah Menengah Johor Bahru - Yahaya, Azizi; Boon, Yusof; Ma’alip, Halimah; Ramli, Jamaludin (2010)
The purpose of this study is to examine the relationship of self-concept and interpersonal communication skill to the academic achievement. The respondence was selected by using simple random consisted of 320 students from eight schools in Johor Bahru picked at random. Assessment instruments used in this study are the “Tennessee Self-Concept Scale” (TSCS) and the “Interpersonal Communication Skills Inventory” (ICSI) in Malay version. The reliability level of the assessment instruments is 0.7498 (TSCS) and 0.7587 got from the pilot study done in a group of twenty respondence. Descriptive statistic and Pearson’s correlation were used to analyse the data. Student’s level of self-concept and interpersonal communication skills is identified. The level of students self concept is positive average or negative. While the student’s interpersonal skill level are high, average or low. Students PMR examination results are use as the academic achievement indicator. The results indicated that majority student’s self-concept and interpersonal communication skill are average. Self-concept was found to correlate significantly with interpersonal communication skills but self-concept was not found to correlate at a significant level with academic achievement. Thus, interpersonal communication skills were found to correlate significantly with academic achievement. Suggestions were made to improve the student’s interpersonal communication skills and their self-concept. One of the suggestions is that the communication skills should be introduced as subject teach in school starting from the primary level to develop self-confidence which indirectly affects students self-concept.